ANALISIS PENGARUH KUAT ARUS LISTRIK DAN WAKTU PROSES ANODIZING PADA OUTER TUBE FRONT FORK MODEL XY TERHADAP KETEBALAN LAPISAN - Nurendra, Rahmadian; Rahmanto, Raden Hengki (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2018)
Anodizing, also known as metal plating, is a surface treatment for coating metal surfaces with aprotective oxide layer of a certain thickness to protect it from environmental destructive effects thatcause corrosion, wear and increase abrasion resistance. The anodizing method also produces amore attractive, textured and colored metal appearance. The purpose of this study was todetermine how the variation of sulfuric acid concentration in aluminum anodizing process to thethickness of the oxide layer and hardness on the aluminum surface.Outertube that has beenmachined is sanded gradually until the aluminum surface is clean and there are no scratches thatcan interfere with the anodizing results. The anodizing process is carried out using a slideregulator transformer, then the cleaning, etching, desmut, anodizing and rinsing processes arecarried out in each process. The anodizing process was carried out using variations in currentstrengths of 0.75A, 1.5A, 2.25A and 3A with 30, 40, 50, and 60 minutes immersion variation times.The tests carried out included a micro photograph of the thickness of the oxide layer.The testresults show that the addition of current strength in the anodizing process affects the thickness ofthe oxide layer.